A Byzantine Pictural Graffito from Jerusalem - Zilberstein, Ayala (Liber Annuus, 2018)
Abstract A pictorial graffito which is incised on a stone board was discovered in soil accumulations in a Byzantine Building from the excavations at the Giv'ati parking lot, south of the Dung gate, Jerusalem. The graffito includes some scenes. In the center of the composition, a large vessel is depicted flanked by a pair of antithetical birds. Two other scenes depict snakes threatening their prey, and a motif of an octagram is also presented on the graffito. The sloppy style of the incisions attests to the work of an amateur rather than a professional artist. Most of the motifs drawn on the plaque from the Givati excavations are well known in the formal art and literature of the Byzantine world. The central motif of an antithetical pair of birds flanking an amphora was a very popular motif in the formal art and was prominent in 'inhabited-scrolls' designs in church mosaics. However, while the graffito's assemblage of faunal motifs is unknown as a whole in the formal visual arts, it is well presented in the Byzantine Christian literature. This paper will deal with the feature of the drawings as well as with the parallels known from the Byzantine formal art and the literature to examine the function of the graffito and to discuss aspects regards the relationships between the folk art and the formal art during Late Antiquity.